Issues and challenges of class F contractors and improvement strategies to survive in Malaysia construction industry - Jeffryl Azniel Adzar, 1976-; Mohamad Ibrahim Mohamad, supervisor; Fakulti Kejuruteraan Awam (2012)
Thesis (Sarjana Sains Pengurusan Pembinaan) - Universiti Teknologi Malaysia, 2012